Incidental diagnosis of Brugada syndrome in a patient initially presenting with acute coronary syndrome in resource-limited settings: A case report - Abdirahman Ibrahim Said; Abdirahman Omer Ali; Abdiwahab Osman said; Mouna Ahmed Abdillahi; Hassan Sh Abdirahman Elmi (Atención Primaria Práctica)
Background: Brugada syndrome (BrS) is a rare, inherited cardiac disorder characterized by distinctive electrocardiographic (ECG) findings, including right bundle branch block and ST-segment elevations in leads V1–V3. It poses significant risks such as ventricular arrhythmias, syncope, and sudden cardiac arrest, with many cases incidentally detected. Chest pain is present in approximately 17% of cases, presenting diagnostic challenges. Case presentation: This report presents a case of BrS in a patient with ischemic heart disease and discusses the management challenges in resource-limited settings. A 58-year-old Somali man presented with sudden-onset chest pain and associated symptoms. His history included ischemic heart disease and an appendectomy. Examination revealed restlessness and diaphoresis, with normal vital signs. Investigations showed normal troponin levels and an ECG indicating ST elevation in lead V1. Managed with acute coronary syndrome (ACS), he was referred for angiography, revealing mild coronary artery disease and normal ventricular function. Follow-up indicated recurrent headaches and financial constraints limited implantable cardioverter–defibrillator (ICD) placement. BrS is associated with an increased risk of ventricular arrhythmias. Discussion and conclusion: Diagnostic challenges include distinguishing it from ACS due to overlapping ECG patterns. Management options are limited, with ICD insertion and quinidine being primary modalities. Resource limitations, such as the lack of ICD services, complicate management. Ongoing debate surrounds the efficacy and safety of beta-blocker therapy. BrS presents diagnostic and therapeutic challenges, emphasizing the need for comprehensive management approaches. Tailored strategies are essential, particularly in resource-limited settings, necessitating further research to optimize patient outcomes. Resumen: Antecedentes: El síndrome de Brugada (BrS) es un trastorno cardíaco hereditario raro, caracterizado por hallazgos electrocardiográficos distintivos, que incluyen bloqueo de rama derecha y elevaciones del segmento ST en las derivaciones V1-V3. Plantea riesgos significativos como arritmias ventriculares, síncope y paro cardíaco súbito, con muchos casos detectados incidentalmente. El dolor torácico está presente en aproximadamente el 17% de los casos, lo que presenta desafíos diagnósticos. Presentación del caso: Este informe presenta un caso de BrS en un paciente con enfermedad cardíaca isquémica y discute los desafíos de manejo en entornos con recursos limitados. Un hombre somalí de 58 años se presentó con dolor torácico de inicio súbito y síntomas asociados. Su historial incluía enfermedad cardíaca isquémica y una apendicectomía. El examen reveló inquietud y diaforesis, con signos vitales normales. Las investigaciones mostraron niveles normales de troponina y un ECG que indicaba elevación del ST en la derivación V1. Manejado como síndrome coronario agudo (SCA), fue referido para angiografía, revelando una enfermedad coronaria leve y una función ventricular normal. El seguimiento indicó dolores de cabeza recurrentes y limitaciones financieras que impedían la colocación de un DAI. El BrS está asociado con un mayor riesgo de arritmias ventriculares. Discusión y conclusión: Los desafíos diagnósticos incluyen distinguirlo del SCA debido a patrones de ECG superpuestos. Las opciones de manejo son limitadas, siendo la inserción de DAI y la quinidina las modalidades principales. Las limitaciones de recursos, como la falta de servicios de DAI, complican el manejo. Existe un debate en curso sobre la eficacia y seguridad de la terapia con betabloqueadores. El BrS presenta desafíos diagnósticos y terapéuticos, enfatizando la necesidad de enfoques de manejo integral. Las estrategias personalizadas son esenciales, particularmente en entornos con recursos limitados, lo que requiere más investigación para optimizar los resultados de los pacientes.